GRIN2A Variants Associated With Idiopathic Generalized Epilepsies - Liu, Xiao-Rong; Xu, Xing-Xing; Lin, Si-Mei; Fan, Cui-Ying; Ye, Ting-Ting; Tang, Bin; Shi, Yi-Wu; Su, Tao; Li, Bing-Mei; Yi, Yong-Hong; Luo, Jian-Hong; Liao, Wei-Ping (Frontiers in Molecular Neuroscience, 2021)
Abstract Objective To explore the role of GRIN2A gene in idiopathic generalized epilepsies and the potential underlying mechanism for phenotypic variation. Methods Whole-exome sequencing was performed in a cohort of 88 patients with idiopathic generalized epilepsies. Electro-physiological alterations of the recombinant N-methyl-D-aspartate receptors (NMDARs) containing GluN2A mutants were examined using two-electrode voltage-clamp recordings. The alterations of protein expression were detected by immunofluorescence staining and biotinylation. Previous studies reported epilepsy-related GRIN2A missense mutations were reviewed. The correlation among phenotypes, functional alterations, and molecular locations was analyzed. Results Three novel heterozygous missense GRIN2A mutations (c.1770A>C/p.K590N, c.2636A>G/p.K879R, and c.3199C>T/p.R1067W) were identified in three unrelated cases. Electrophysiological analysis demonstrated R1067W significantly increased the current density of GluN1/GluN2A NMDARs. Immunofluorescence staining indicated GluN2A mutants had abundant distribution in the membrane and cytoplasm. Western blotting showed the ratios of surface/total expression of the three GluN2A-mutants were significantly increased comparing to the wild type. Further analysis on the reported missense mutations demonstrated that mutations with severe gain-of-function were associated with epileptic encephalopathy, while mutations with mild gain of function were associated with mild phenotypes, suggesting a quantitative correlation between gain-of-function and phenotypic severity. The mutations located around transmembrane domains were more frequently associated with severe phenotypes and absence seizure-related mutations were mostly located in carboxyl-terminal domain, suggesting molecular sub-regional effects. Significance This study revealed GRIN2A gene was potentially a candidate pathogenic gene of idiopathic generalized epilepsies. The functional quantitative correlation and the molecular sub-regional implication of mutations helped explaining the relatively mild clinical phenotypes and incomplete penetrance associated with GRIN2A variants.